THE DEVELOPMENT OF TRAINING PROGRAM AND TEACHING ENGLISH FOR SECOND KEY STAGE TEACHERS IN NAKHON RATCHASIMA - เลิศไธสง, มาลินี (Academic Journal Phranakhon Rajabhat University, 2018)
This research was aimed 1) to obtain the fundamental information to develop a training program on teaching English by Active Learning for the second key stage teachers in Nakhon Ratchasima Province 2) to develop a training program on teaching English by Active Learning for the second key stage teachers in Nakhon Ratchasima Province 3) to implement a training program on teaching English by Active Learning for the second key stage teachers in Nakhon Ratchasima Province. The research method consisted of 4 steps including 1) studying the fundamental information 2) developing a training program 3) trial of the training program and 4) evaluating the usage of the training program. A group of trainees were 100 English teachers in Nakhon Ratchasima for the second key stage teachers of Primary Educational Service Area Office 2.One Group Pretest-Posttest Design was used to compare the difference of knowledge, understanding of the program and English teaching scores before and after the training. A questionnaire was used to inquire comment about the training program. Then, the result was analyzed by using average, Standard Deviation, t-test dependent and found that: 1. The training program on teaching English by Active Learning for teachers contained objectives, content, training method, tools and materials, measurement and evaluation. The program content included 1) theoretical concept of the program 2) concept and theory of learning arrangement in the 21st century 3) English learning arrangement by using Active Learning and 4) Lesson plan of English learning arrangement and example of lesson plan. 2. Before and after the training, the English teachers had different knowledge and understanding in the English training on teaching English by Active Learning in a significant level of .05, which means having more knowledge and understanding. 3. The training participants felt that the program was appropriate in every aspect and in a high level (X = 4.19) and that they can apply it for improving and developing their teaching to be more effective.